Benzo[a]pyrene exposure prevents high fat diet-induced obesity in the 4T1 model of mammary carcinoma - Gonzalez-Pons, Romina; Bernard, Jamie J. (Frontiers in Oncology, 2024)
Tumor metastasis is the main cause of death in triple-negative breast cancer (TNBC) patients. TNBC is the most aggressive subtype of breast cancer lacking the expression of estrogen, progesterone, and human epidermal growth factor 2 receptors, thereby rendering it insensitive to targeted therapies. It has been well-established that excess adiposity contributes to the progression of TNBC; however, due to the aggressive nature of this breast cancer subtype, it is imperative to determine how multiple factors can contribute to progression. Therefore, we aimed to investigate if exposure to an environmental carcinogen could impact a pre-existing obesity-promoted cancer. We utilized a spontaneous lung metastatic mouse model where 4T1 breast tumor cells are injected into the mammary gland of BALB/c mice. Feeding a high fat diet (HFD) in this model has been shown to promote tumor growth and metastasis. Herein, we tested the effects of both a HFD and benzo(a)pyrene (B[a]P) exposure. Our results indicate that diet and B[a]P had no tumor promotional interaction. However, unexpectedly, our findings reveal an inhibitory effect of B[a]P on body weight, adipose tissue deposition, and tumor volume at time of sacrifice specifically under HFD conditions.